Assessing livelihood vulnerability and adaptation to climate variability and change among farming households in Plateau State, north-central Nigeria - Hassan, Buhari (University of the Witwatersrand, Johannesburg, 2024)
It has been projected that sub-Saharan Africa would be severely affected by climate change in form of persistent and increasing climate variability. Nigeria’s situation as a developing country coupled with the fact that agricultural activities are primarily rainfed, provides a suitable case study in which to assess the vulnerability of farming households to climate variability and change. Lack of data on the nature and extent of vulnerability to climate variability (particularly annual changes in rainfall and temperature patterns) on food production systems and livelihoods in Nigeria hinders the development of effective policies to mitigate the adverse impacts of climate change and variability. The study aims to improve understanding of the socio-economic, institutional, biological and physical factors that contribute to vulnerability of farming households to climate change and variability in Nigeria. By combining descriptive, participatory and statistical analysis as well as field observations, this research develops a holistic approach to assess the level of exposure, sensitivity and adaptive capacity of farming households. Multistage sampling was used to purposely select communities in Bokkos Local Government Area, Plateau State, for the study, while farming households were randomly selected for the household questionnaire survey within four communities. Purposive sampling was used to identify key informants for interviews. Observation and taking photographs of farmers’ activities were used to complement the other data collection methods. Qualitative data was analysed using descriptive and content analysis, while the quantitative data was analysed using the Statistical Package for Social Sciences (SPSS) (v 27) and Microsoft Excel (v2020). The level of vulnerability of farming households was determined using the Sustainable Livelihood Approach. Results show that farmers are exposed to climate variability in form of changing rainfall patterns which includes late onset of rains, dry spells, and early cessation of rains and crop loss due to pests and disease infestation. Results show that the vulnerability of farming households can be linked to access to household livelihood capital assets and that households are characterised by low levels of financial, social and physical capital. Smallholder farming households adopt a range of on-farm and off-farm adaptation strategies including changing planting time, crop diversification, engaging in irrigation farming, intensifying the use of fertilizers, manure and agro-chemicals to boost crop yield, and planting of disease-resistant and drought-tolerant crop varieties. Farming households experience a number of challenges which include a lack of financial resources which has a strong influence on enhancing other capital assets such as physical and natural capitals; poor access to mechanised agricultural equipment, lack of training on how to deal with climate change and variability, limited access to improved crop varieties as well as a lack of institutional support, which constitute serious barriers to adaptation to climate variability. In applying these results to climate change adaptation it is recommended that policymakers need to institute specific and implementable climate change adaptation policies that will enable farmers to utilize their capital assets on effective adaptation measures and also engage in viable alternative livelihood diversification strategies, enhance agricultural productivity and resilience and improve institutional support including access to information and training
A research report submitted in partial fulfillment of the requirements for the Doctor of Philosophy to the Faculty of Science, School of geography, archaeology & environmental studies, University of the Witwatersrand, Johannesburg, 2024
Keywords: Rural livelihoods; Vulnerability; Adaptation; Climate variability; Diversification; Resilience; UCTD; SDG-13: Climate action